Road Traffic Accident Traumatic Vehicle Seat Belt Abdominal Wall Hernia - Mahmoud R. Manasra; Roua E. Farah; Arein A. Abufara; Bara M. AbuIrayyeh; Rahaf E. Farah; Mohammed A. Maraqa (Case Reports in Surgery)
Traumatic abdominal wall hernia (TAWH) is a rare type of hernia with an incidence of about <1.5%, resulting from blunt abdominal trauma, which leads to an increase in the intra-abdominal pressure and rupture in the abdominal musculature and fascia with herniation of the abdominal organs into the defect. Most TAWH contained either a small bowel (69%) or a large bowel (36%), with 16% containing both. This condition is often not present as an isolated case, as 30% to 60% of the cases are accompanied by other intra-abdominal injuries. The typical manner of presentation is a tender subcutaneous swelling across the abdomen wall with overlaying bruising and ecchymosis. The radiological investigative modality of CT scan has the highest index of diagnosing accompanied intra-abdominal visceral injuries. We present a rare case of a 23-year-old male patient diagnosed with TAWH containing both small bowel and sigmoid colon associated with psoas hematoma caused by a seat belt postroad traffic accident (RTA).